A case where Barro expectations are not rational - Ekkehart Schlicht (Kiel Institute for the World Economy (IfW), 2012)
The paper generalizes Feldstein's criticism (Perceived Wealth in Bonds and Social Security, 1976) of Barro's analysis (Are Government Bonds Real Net Wealth?, 1974) for the case that the interest rate exceeds the growth rate. This is done by considering an economy in steady state where all agents hold Barro expectations: they believe that government debt must necessarily be repaid and therefore leave the present value of their income streams unchanged. In this scenario, a change in the mode of taxation affects the present value of disposable income in the private sector. This violates their Barro expectations.
Keywords: E2; E12; E6; H6; 330; Barro-Ricardo equivalence; Ricardian equivalence; fiscal policy; debt; taxation; rational expectations; Ricardianisches Äquivalenztheorem; Öffentliche Anleihe; Zins; Rationale Erwartung; Steuerpolitik; Steuerwirkung; Erwartungstheorie; Theorie